A macro-scale experimental study of sub- and super-critical CO2 flow behaviour in Victorian brown coal. (15th October 2015) - Ranathunga, A.S.; Perera, M.S.A.; Ranjith, P.G.; Ju, Y.; Vishal, V.; De Silva, P.N.K.
Highlights: Sub- and super-critical CO2 flow behaviours in Victorian brown coal. Testing of macro scale samples using an advanced core-flooding apparatus. CO2 adsorption induced swelling causes significant coal structure modification. Super-critical CO2 injection causes a greater reduction in CO2 permeability. CO2 phase and pressure influences on coal matrix swelling and flow properties. Abstract: In deep coal seams carbon dioxide (CO2 ) exists in its super-critical state, which emphasizes the importance of studying super-critical CO2 flow behaviour in coal, especially for field applications, such as CO2 sequestration and enhanced coal bed methane recovery. Although there has been some research on the subject, the studies have been conducted on only certain types of coal (e.g., naturally fractured black coal) using small coal samples, which makes it difficult to verify the applicability of adsorption theories at a higher scale to estimate field CO2 storage capacity. The main objective of this study is therefore to determine the permeability behaviour of coal for sub-critical and super-critical CO2 flows using large coal specimens (203 mm in diameter and 1000 mm in length). A series of core flooding experiments was conducted on brown coal specimens collected from the Latrobe Valley basin, Victoria, using an advanced core flooding apparatus, for a range of injection pressures (6–10 MPa) at 11 MPa axial stress and 38 °C temperature. According to the test results, CO2 permeability in coal may reduce with increasing injection pressure due to the phase transition of CO2 from sub-critical to super-critical during pressure increment. N2 injection into a coal mass permeated with CO2 shows lower permeability values compared to N2 injection into a fresh coal mass, because in the former case, the coal mass structure has already been critically reformed during the CO2 flood. Although the pressure development trends for first N2, CO2 and second N2 injections along the sample are similar, there may be a noticeable pressure reduction, especially closer to the injection point during the second N2 injection. This is due to the coal structure re-arrangement during the CO2 flood, where the pressure development is less in the regions, when CO2 is in the super-critical state. Such CO2 and N2 migration patterns through coal seams after injection are highly important for field applications.